A new algorithm to measure relevance among Web pages - Sadi, M.S.; Rahman, M.M. Hafizur; Horiguchi, Susumu (WIT Press, 2006)
This paper proposes a new algorithm to measure relevance among Web pages (RWP) using a hybrid method of hyperlink analysis and content analysis. Here we used a new approach to Web searching where the input to the search process is not a set of query terms, rather the URL of a page, and the output is a set of related Web pages. A related Web page is one that addresses the same topic as the original page. Here, the proposed algorithm first uses only the connectivity information in the Web (i.e., the links between pages) and then the content of pages. To evaluate the performance, the algorithm is compared with existing algorithms. Experimental results show that RWP outperforms existing algorithms to find relevant Web pages. RWP increases the search efficiency effectively and enhances the application area of Web related research.